Significance of professional values in nursing teachers and students, UNMSM - 2014 - Vera, Martha (2016)
Objective. To interpret the significance of professional values in students and teachers of the Nursing School at Universidad Nacional Mayor de San Marcos. Methods. Qualitative, descriptive-interpretative study. The analysis was ideographic and nomothetic. Sample by saturation criterion, and in depth interview to 12 teachers and 16 students of 4th and 5th year of studies assembled in three focus groups. Results. By objectification and anchoring and within the academic and administrative environment, the social representation of the meaning of professional values emerged in five categories and subcategories. In Teachers: having personal values: love, respect, professional vocation, responsibility and friendship, and values inherent to the professional work: love, responsibility, respect, intellectual ability, justice, and social commitment. In Students: having personal values: love, respect, friendship; and values inherent to the professional work: developing and consolidating the vocation; taking scientific knowledge, love, respect, friendship, responsibility, justice, punctuality. Conclusions. For teachers and students professional values were based on personal moral and ethical values inherent to the professional work, including love, dedication, responsibility, respect, friendship, justice, scientific knowledge, learning values by example and teachers as models.